2016
DOI: 10.2474/trol.11.474
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Effect of Recesses on Conical Hybrid Journal Bearing Compensated with CFV under Micropolar Fluid Lubrication

Abstract: This paper theoretically presents the comparative performances of conical hybrid journal bearing with 4-pockets and 6-pockets compensated with constant flow valve (CFV) under micropolar fluid lubrication for various semi-cone angles. The numerical solution of the modified Reynolds equation for micropolar fluid flow on the conical surface has been done by using finite element method using Galerkin's technique along with the necessary boundary conditions and iterative scheme. The bearing performances have been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The stability of the rigid rotor supported by six recessed hybrid bearings with orifice compensation and influence of restrictor design parameters and eccentricity on it are studied by Chen et al [13]. Rana et al [14,15] have analyzed the performance of four and six pockets conical hybrid journal bearing. The performances of conical hybrid journal bearing with constant flow valve for micropolar lubricant for different load arrangements have not been exploited by the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the rigid rotor supported by six recessed hybrid bearings with orifice compensation and influence of restrictor design parameters and eccentricity on it are studied by Chen et al [13]. Rana et al [14,15] have analyzed the performance of four and six pockets conical hybrid journal bearing. The performances of conical hybrid journal bearing with constant flow valve for micropolar lubricant for different load arrangements have not been exploited by the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Bansal et al [22] highlighted elastic distortion effects on stability of micropolar lubricated hydrodynamic bearing and their results indicated that increase in flexibility causes decrease in stability. Various studies concerning the theory of micropolar lubricant and effects of micropolar parameters on performance and stability of journal bearings have also been reported in literature [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Verma et al [11,12] analyzed and compared performance characteristics of flexible multirecess capillary and CFV compensated hydrostatic journal bearing operating with micropolar lubricant and observed a significant influence of bearing shell flexibility and micropolar effect on bearing performance. Recent studies on journal bearings operating with micropolar lubricant by Ram et al [13] and Rana et al [14] demonstrated the influence of micropolar parameters on performance characteristics of journal bearings.…”
Section: Introductionmentioning
confidence: 99%